Uncovering plagiarism in academic writing : developing authorial voice within multivoiced text - Angelil-Carter, Shelley (Rhodes University, Faculty of Education, Department of Education, 1996)
Plagiarism is a modern Western construct which arose with the introduction of copyright laws in the eighteenth century. Before this time, there was little sense of artistic "ownership". Since then, the ideas of "originality" in writing as well as the "autonomous text" have been highly valued. In the theoretical section of this dissertation I deal with plagiarism and referencing from three perspectives. After looking at problems of definition of plagiarism, I turn to the first perspective, the historical development of the notions of plagiarism and originality. Alongside this I discuss the notions of "autonomous text" and "decontextualized" language, and attempt to show that these concepts are problematic, and that language is intensely social at the levels of discourses, genres, and the word. The second angle is a snapshot of present-day writing genres, and how they deal with documentation in different ways. The third point of focus is on the development of the student writer, on whom present-day genres of academic writing, and the historically constructed notions of plagiarism converge. Here I centre on the development of the undergraduate student as a writer, and some of the things that may be happening when a student is seen to be plagiarizing. Some of these are the "alienness" of academic discourses, the hybridization of discourses, the need to "try on" academic discourses, the lack of authority of the student writer and her relationship to the authority of the sources, and the way in which languages are learned and reproduced in chunks. I look finally at what the meaning of authorship might be in an intensely social view of language, and at the complexity of developing authorial voice in writing. The dissertation is located in a postpositivist paradigm, and seeks to interpret as well as being oriented towards praxis. The research took place within the Political Studies Department at the University of Cape Town. The study included a discourse analysis of the departmental handbook, as well as analysis of academic essays, at the first year and third year level, which were selected for having problems with referencing, or having plagiarized. A few were selected for good referencing. Students who had written these essays, and tutors and lecturers who had marked them, were then interviewed. In the analysis I explore differing understandings of the role of referencing in the academic essay, what negative and positive consequences the practice of referencing and the monitoring of plagiarism have, with regard to authority and voice in student writing, what might be happening when students are thought to be plagiarizing, and what difficulties are experienced by students in developing an authorial voice when using multiple sources. The study found that there are a range of underlying causes for plagiarism in student writing, which indicate that plagiarism is more a problem of academic literacy than academic dishonesty. It also found that marking practices in detecting plagiarism may sometimes be based on problematic assumptions about the amount of background knowledge and independent ideas which students bring to their writing. I conclude by putting forward a pedagogy for plagiarism and referencing, which is based on 1) the negotiation of shared meaning around the concept of plagiarism, including an examination of assumptions linked to this concept in its monitoring and enforcement, leading to the development of written policy and guidelines emerging from this shared understanding. 2) The development of an academic literacy programme within the curriculum, with attention to the complexities of developing authorial voice whilst constructing a text based on the texts of others, with a focus on authors, which moves students towards an understanding of how knowledge is constructed.
Keywords: Plagiarism -- Research; Academic writing -- Research